2016
DOI: 10.17221/633/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Study on some soil quality changes obtained from long-term experiments

Abstract: Agricultural practice often causes soil structure degradation and as a result it leads to changes in soil fertility and quality. The aim of this study was to compare soil aggregate stability (SAS) and soil organic matter (OM) quantity and quality in different systems of soil management. Three adjoining longterm experiments established on Chernozem were chosen; they were all set up in different years with different crop rotations and comparable fertilization treatments: control (without fertilization); NPK; man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(18 reference statements)
1
10
0
1
Order By: Relevance
“…Across all assessed soils, the quality of labile SOM appears to be improved under complex crop rotations, and the labile SOM pool seems to be more utilized and cycled by soil microbial communities. In this context, a greater quality of labile SOM implies enhanced bioavailability and decomposability of the POM fraction as indicated by narrower C:N ratios (Bu et al 2015;Castro et al 2015;Stehlíková et al 2016), suggesting that utilization of this labile SOM by microbes is propensive to occur. Moreover, it is noteworthy that although the forest soil had much higher SOM concentration than both simple and complex rotations, the MBC values in forest land was the lowest among all these land use systems, with 1.5 times significantly lower MBC in the forest soil than under the complex rotation (Table 1), which may reflect that the soil microorganisms could have limited access to decompose SOM in forest land.…”
Section: Complex Rotations Alter Som Pools and Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all assessed soils, the quality of labile SOM appears to be improved under complex crop rotations, and the labile SOM pool seems to be more utilized and cycled by soil microbial communities. In this context, a greater quality of labile SOM implies enhanced bioavailability and decomposability of the POM fraction as indicated by narrower C:N ratios (Bu et al 2015;Castro et al 2015;Stehlíková et al 2016), suggesting that utilization of this labile SOM by microbes is propensive to occur. Moreover, it is noteworthy that although the forest soil had much higher SOM concentration than both simple and complex rotations, the MBC values in forest land was the lowest among all these land use systems, with 1.5 times significantly lower MBC in the forest soil than under the complex rotation (Table 1), which may reflect that the soil microorganisms could have limited access to decompose SOM in forest land.…”
Section: Complex Rotations Alter Som Pools and Partitioningmentioning
confidence: 99%
“…An earlier study showed that manure addition can increase both the root and microbial biomass debris which are both key contributing factors of soil POM (Purakayastha et al 2008). Likewise, long-term additions of manure have been shown to favor soil carbon cycling and macroaggregate formation (Liu et al 2013;Stehlíková et al 2016). While manure adds carbon directly to the soil profile, balanced fertilization supports plant growth and biomass production which subsequently feedbacks into increased plant residues leading to long-term accretion of SOM (Hati et al 2008).…”
Section: Nutrient Additions Lead To Varying Enhancements In Som Dynamicsmentioning
confidence: 99%
“…Improvement was also observed for sugar content (Prugar et al 2008). The importance of proper crop rotation and structure, and associated long-term changes in soil properties, are pointed out by Stehlíková et al (2015). Mühlbachová et al (2015) stresses new, soil-protecting tilling methods and their use.…”
mentioning
confidence: 99%
“…Alberga numerosas y diversas especies microbianas, animales y vegetales responsables de la actividad metabólica, esencial para la formación, funcionamiento y fertilidad del mismo. Sin embargo, los diferentes sistemas de uso de los suelos ocasionan diferentes grados de perturbación (Navarro et al, 2018;Rosa et al, 2017), afectando sus características físicas, químicas y biológicas, que generan efectos como la degradación y erosión de la estructura del suelo y conducen a cambios en la fertilidad y calidad del suelo (Stehlíková et al, 2016).…”
Section: Introductionunclassified